Calm in the midst of cytokine storm: a collaborative approach to the diagnosis and treatment of hemophagocytic lymphohistiocytosis and macrophage activation syndrome - BARIŞ, HATİCE EZGİ (BMC, 2019)
Hemophagocytic lymphohistiocytosis (HLH) and macrophage activation syndrome (MAS) were historically thought to be distinct entities, often managed in isolation. In fact, these conditions are closely related. A collaborative approach, which incorporates expertise from subspecialties that previously treated HLH/MAS independently, is needed. We leveraged quality improvement (QI) techniques in the form of an Evidence-Based Guideline (EBG) to build consensus across disciplines on the diagnosis and treatment of HLH/MAS. A multidisciplinary work group was convened that met monthly to develop the HLH/MAS EBG. Literature review and expert opinion were used to develop a management strategy for HLH/MAS. The EBG was implemented, and quality metrics were selected to monitor outcomes. An HLH/MAS clinical team was formed with representatives from subspecialties involved in the care of patients with HLH/MAS. Broad entry criteria for the HLH/MAS EBG were established and included fever and ferritin ae500 ng/mL. The rheumatology team was identified as the gate-keeper, charged with overseeing the diagnostic evaluation recommended in the EBG. First-line medications were recommended based on the acuity of illness and risk of concurrent infection. Quality metrics to be tracked prospectively based on time to initiation of treatment and clinical response were selected. HLH/MAS are increasingly considered to be a spectrum of related conditions, and joint management across subspecialties could improve patient outcomes. Our experience in creating a multidisciplinary approach to HLH/MAS management can serve as a model for care at other institutions.
Keywords: Macrophage activation syndrome (MAS); Hemophagocytic lymphohistiocytosis (HLH); Quality improvement research; Evidence-based guideline; JUVENILE IDIOPATHIC ARTHRITIS; ONSET STILLS-DISEASE; INTERFERON-GAMMA; RHEUMATOID-ARTHRITIS; CASE SERIES; T-CELLS; INTERLEUKIN-18; SECONDARY; ANAKINRA; FERRITIN